PENERAPAN CUSTOMER SATISFACTION INDEX (CSI) DAN ANALISIS GAP PADA KUALITAS PELAYANAN KEFARMASIAN DI APOTEK SEHAT BERSAMA 2 JAKARTA TIMUR - Brahmono, Angga; Susanto, Yugo; Widiyanto, Rahmat; Erzania, Reyfana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Health quality assurance is a very important and fundamental approach or effort in providing health services. One form of service quality in the health service sector is pharmaceutical services in pharmacies. Satisfaction is an important part of pharmaceutical services because it is useful for improving medical health service outcomes. The aim of this research is to analyze customer satisfaction and expectations regarding the performance of pharmaceutical services at Apotek Sehat Bersama 2. The methods used in this research are the Customer Satisfaction Index (CSI) method and Gap Analysis. This research method is a survey, namely by distributing questionnaires to pharmacy customers. The sampling technique was carried out by accidental sampling with 188 respondents. The scale used is a Likert scale based on the level of satisfaction and expectations. The research results show that the Customer Satisfaction Index (CSI) value for customer satisfaction level is 82.4%, which is included in the very satisfied criteria. The highest gap value is an indicator that pharmacy staff understand customer complaints, provide drug/health information clearly and easily understood, always provide information on how to use drugs requested by customers, pharmacy staff are always polite and friendly in providing service to customers and pharmacy staff provide information on usage rules. drugs and side effects that may arise as well as the lowest gap value is that the drug requested by the customer is always available.